Fabrication of ultrathin nanocellulose shells on tough microparticles via an emulsion-templated colloidal assembly: towards versatile carrier materials. Issue 32 (12th July 2019) - Fujisawa, Shuji; Togawa, Eiji; Kuroda, Katsushi; Saito, Tsuguyuki; Isogai, Akira
Abstract : Ultrathin nanocellulose shells are constructed on the surface of polymer microparticles by an emulsion-templated self-assembly. The shell renders the microparticles biocompatible and highly dispersible in water with molecular recognition properties. Abstract : Here, we develop a robust approach to forming an ∼8 nm thick cellulose nanofiber (CNF) shell on polymer microparticles through an emulsion-templated assembly. The median diameter of the CNF-shelled microparticles was 3.0 μm. The microparticles showed good dispersibility in water with a ζ-potential of −46.7 ± 0.5 mV and had good mechanical resistance. The surface CNF shells showed pH-sensitive drug loading/releasing properties, which suggest potential for a range of therapeutic and biomedical applications.